The Li and Co-Substituted Spinel Mn Oxide, (Li)8a[Lix/4Co3x/4Mn2−x]16dO4, and Its Use as Cathode Material in Flat and Flexible Lithium Battery. (2000) - Hong, Y. S.; Han, C. H.; Kim, K.; Kwon, C. W.; Campet, G.
Abstract : The partial substitution of manganese by lithium and cobalt ions in 16d octahedral sites enhances the electrochemical cyclability of LiMn2 O4 upon cycling. The improvement in cycling performance is mainly attributed to the suppression of the Jahn–Teller distortion in the spinel structure. The as-doped spinel Mn oxide has been successfully used as cathode material in flat and flexible lithium battery.